2014
DOI: 10.3109/10715762.2014.987274
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effects of β-hydroxybutyrate on Aβ-injected rat hippocampus in vivo and in Aβ-treated PC-12 cells in vitro

Abstract: Alzheimer's disease is a neurodegenerative disorder associated with the deposition of the peptide amyloid-beta (Aβ) in senile plaques and cerebral vasculature. The neurotoxic mechanisms of this condition have been linked to oxidative-stress-induced apoptosis leading to widespread neuronal loss. Herein, we demonstrate the neuroprotective effects of a ketone body D-β-hydroxybutyrate (β-HB) in neural cell lines and an animal model induced by injecting Aβ into the hippocampus. Using histological examination and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Experiments showed that BHB decreased K + efflux and endoplasmic reticulum stress (Youm et al, 2015; Bae et al, 2016). Furthermore, BHB is transported to brain parenchyma and plays a neuroprotective role under several pathological conditions (Orhan et al, 2015; Xie et al, 2015). …”
Section: Targeting the Nlrp3 Inflammasome For The Treatment Of Neurolmentioning
confidence: 99%
“…Experiments showed that BHB decreased K + efflux and endoplasmic reticulum stress (Youm et al, 2015; Bae et al, 2016). Furthermore, BHB is transported to brain parenchyma and plays a neuroprotective role under several pathological conditions (Orhan et al, 2015; Xie et al, 2015). …”
Section: Targeting the Nlrp3 Inflammasome For The Treatment Of Neurolmentioning
confidence: 99%
“…BHB disrupted ASC oligomerization and speck formation, prevented K + efflux, and reduced endoplasmic reticulum (ER) stress. Moreover, BHB crossed the BBB and had a neuroprotective effect in an animal model of Aβ‐induced neurodegeneration and traumatic brain injury (Supplemental Table) …”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…A number of recent papers have used what they refer to as an acute model of AD by directly injecting Aβ(1–40) or Aβ(1-42) into the hippocampus. When compounds were administered prior to the injection of Aβ, beneficial effects were noted for SuHeXiang essential oil [89], sulforaphane [90, 91], β-hydoxybutyrate [92], orientin [93], and baicalin [94]. A major caveat to all the studies discussed in this section is that none of them were done in Nrf2−/− or knockdown mice to clearly demonstrate that these same compounds being tested require Nrf2 for their therapeutic effects.…”
Section: Nrf2 In Alzheimer's Diseasementioning
confidence: 99%